(untitled) (Journal of Hama University, 2019)
Linear piezoelectric motor (LPZM) is a kind of motor which offers high precision and fast response. It is widely used in industrial and medical applications, surgical instruments and robots, etc. In this article, we present an analytical study and modeling of a linear piezoelectric motor with system drive using Fuzzy PID controller. Firstly, a dynamic model of the linear piezoelectric motor was developed based on the motion equations of the sliding part of the motor. Secondly, the drive system was designed based on the traditional PID controller. It’s parameters were calibrated to obtain the best possible response for speed and position signals, However, the purpose of using the motor in high precision applications requires a more precise control and faster response than traditional controllers. An intelligent controller based on Fuzzy PID was selected because the nonlinearity relationship between the current and position displacement. During the design process of the Fuzzy PID controller, we determined the degree of input belonging to the fuzzy input groups and determining the output gain according to the control law applied to the system. On the other hand, the controller has been built sur Matlab/Simulink environment. This developed driving system controls both speed and position for the motor.The results have been shown that the Fuzzy PID controller is faster response from the classical controller by 1.2 milliseconds, which confirm the importance of Fuzzy PID in terms of speed and performance to stability.